2022
DOI: 10.1093/nar/gkac755
|View full text |Cite
|
Sign up to set email alerts
|

OCT4 interprets and enhances nucleosome flexibility

Abstract: Pioneer transcription factors are proteins that induce cellular identity transitions by binding to inaccessible regions of DNA in nuclear chromatin. They contribute to chromatin opening and recruit other factors to regulatory DNA elements. The structural features and dynamics modulating their interaction with nucleosomes are still unresolved. From a combination of experiments and molecular simulations, we reveal here how the pioneer factor and master regulator of pluripotency, Oct4, interprets and enhances nuc… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
3

Relationship

2
8

Authors

Journals

citations
Cited by 22 publications
(8 citation statements)
references
References 68 publications
0
7
0
Order By: Relevance
“…For example, two recent cryo-EM structures of the pioneer transcription factor SOX2-nucleosome complexes showed different mechanisms of binding 21,22 . All this complicates the identification and characterization of human pioneer transcription factors pointing to the pressing need to develop predictors and classifiers 49,6769 .…”
Section: Discussionmentioning
confidence: 99%
“…For example, two recent cryo-EM structures of the pioneer transcription factor SOX2-nucleosome complexes showed different mechanisms of binding 21,22 . All this complicates the identification and characterization of human pioneer transcription factors pointing to the pressing need to develop predictors and classifiers 49,6769 .…”
Section: Discussionmentioning
confidence: 99%
“…This has prompted speculations that Oct4 engages closed chromatin with just one of its domains 47 or even that POU S alone is involved in chromatin opening 51 . On the other hand, we showed that while Oct4 uses either the POU S and POU HD to recognize specific sequences on nucleosomes, the other domain scans unspecifically creating barriers to nucleosome closing 52 . The data presented here shows that removing POU HD abolishes both Oct4 DNA binding on SoxOct motifs (Fig.…”
Section: Resultsmentioning
confidence: 93%
“…The atomic resolution provided clues that the amplitude of nucleosome motions such as breathing and twisting were increased by the binding of Oct4 to multiple TF binding sites with a higher local structural flexibility [ 108 ]. A detailed regulatory mechanism of nucleosome dynamics by TF was proposed by MacCarthy et al, who suggested that Oct4 altered the optimal wrapping of the two gyres around each other and the histones but did not mediate nucleosome opening [ 109 ]. It has been indicated that intrinsic nucleosome flexibility is important for Oct4 binding, and the magnitude of Oct4’s impact on nucleosome dynamics is dependent on the binding site position and the mobility of histone tails.…”
Section: Multiple Regulatory Factors and Associated Mechanismmentioning
confidence: 99%